The Influence of Penny Stocks on the Pricing of Companies Quoted on theWarsaw Stock Exchange in the Context of the ICAPM - Urbański, Stanisław (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The paper attempts to explain the impact of penny stock on pricing in light ofthe ICAPM as stock exchanges introduce restrictions on penny stocks trading.The study is conducted using stocks listed on the Warsaw Stock Exchange (WSE)between 1995–2012. The systematic risk and risk prices components are simulated by two chosen ICAPM applications, using different procedures of portfolio construction.The main market WSE stocks are sorted into queintile portfolios usingtwo procedures. It is assumed that elimination of penny stocks contributes to morecorrect pricing, observed with ICAPM validity, however only when simulatingalgorithm uses appropriate construction of tested portfolios. The tests were carriedout in four modes. All WSE stocks were analyzed in mode 1. Penny stockswith market values lower than 1.50, 5.00 and 10.00 PLN were excluded from thestudy in modes 2, 3 and 4. The analysis indicates that the results are in line withthe extended conjectures.